2012
DOI: 10.1590/s0100-879x2012007500135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chromosomal abnormalities by cIg-FISH and association with proliferative and apoptotic indexes in multiple myeloma

Abstract: Eighty-six newly diagnosed multiple myeloma (MM) patients from a public hospital of São Paulo (Brazil) were evaluated by cIg-FISH for the presence of del(13)(q14), t(4;14)(p16.3;q32) and del(17)(p13). These abnormalities were observed in 46.5, 9.3, and 7.0% of the patients, respectively. In order to identify the possible role of del(13)(q14) in the physiopathology of MM, we investigated the association between this abnormality and the proliferative and apoptotic indexes of plasma cells. When cases demonstratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In the present study, the frequencies of t(11;14), t(4;14) and del(13q) were in agreement with previous studies ( 3 , 11 12 13 14 ), whereas t(14;16) and del(17p) were observed in lower frequencies than in other series ( 3 , 11 , 15 ). In a previous study from Brazil ( 15 ), the frequencies of t(11;14), del(13q) and del(17p) were similar to the ones herein reported, while a higher frequency of t(4;14) was found in our study (14.1% vs 9.3% in the mentioned study) ( 15 ). The frequency of t(14;16) has not yet been reported for Brazilian patients.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the frequencies of t(11;14), t(4;14) and del(13q) were in agreement with previous studies ( 3 , 11 12 13 14 ), whereas t(14;16) and del(17p) were observed in lower frequencies than in other series ( 3 , 11 , 15 ). In a previous study from Brazil ( 15 ), the frequencies of t(11;14), del(13q) and del(17p) were similar to the ones herein reported, while a higher frequency of t(4;14) was found in our study (14.1% vs 9.3% in the mentioned study) ( 15 ). The frequency of t(14;16) has not yet been reported for Brazilian patients.…”
Section: Discussionsupporting
confidence: 93%
“… 15 This technique, which also requires a long time for training and does not have good reproducibility, was used in two Brazilian studies. 18 , 19 The third approach is by selecting cells either by flow cytometry or immunomagnetic bead-based PC sorting. 4 …”
Section: Discussionmentioning
confidence: 99%
“…1q amplification, t(4;14), t(14;16) and 17p13 deletion are associated with bad prognoses, 4 , 8 , 12 , 21 and the 13q deletion is still controversial. 18 In particular, t(4;14)(p16;q32) at diagnosis has been shown as a bad prognostic marker, 18 even in smoldering MM 22 , 23 and in patients with symptomatic MM treated with conventional chemotherapy, which may be ameliorated with bortezomib-based combinations. 2 …”
Section: Discussionmentioning
confidence: 99%
“…In the southern regions of Brazil, where genetic alterations have been studied in MM, no such bias was described. 7 …”
mentioning
confidence: 99%